Pulsed Nd:YAG laser depositions of ITO and DLC films for OLED applications - YONG, T; YAP, S; SAFRAN, G; TOU, T (ELSEVIER SCIENCE BV, 2007)
Indium-tin oxide (ITO) films deposited on heated and non-heated glass substrate's by a pulsed Nd:YAG laser at 355 nm and similar to 2.5 j/cm(2) were used in the fabrication of simple organic light-emitting diodes (OLEDs), ITO/(PVK + Alq(3) + TPD)/Al. The ITO was deposited on heated glass substrates which possessed resistivity as low as similar to 3 x 10(-4) Omega CM, optical transmission as high as similar to 92% and carrier concentration of about similar to 5 x 10(20) cm(-3), were comparable to the commercial ITO. Substrate heating transformed the ITO microstructure from amorphous to polycrystalline, as revealed by the XRD spectrum. While the polycrystalline ITO produced higher OLED brightness, it was still lower than that on the commercial ITO due to surface roughness. A DLC layer of similar to 1.5 nm deposited on this ITO at laser fluence of > 12.5 J/cm(2) improved its device brightness by suppressing the surface roughness effect. (c) 2006 Elsevier B.V All rights reserved.